Determination of Fibrinogen and Fibrinogenolytic Activity - Nilsson, Inga Marie; Olow, Bertil (Thrombosis and Haemostasis, 1962)
A method for determining plasma fibrinogen and fibrinogenolytic activity, with epsilonaminocaproic acid (ε-ACA) as an inhibitor of fibrinolysis, in patients with high fibrinolytic activity, is described in detail.The fibrinogen was determined by a modification of Morrison’s syneresis method in parallel in 1. citrated plasma that was incubated for 2 hours at 37° C, after which further digestion was prevented by addition of ε-ACA and is referred to as fibrinogen A, and 2. in citrated plasma prepared from blood collected in tubes containing ε-ACA to prevent activation of plasminogen and is referred to as fibrinogen B.The difference between fibrinogen B and fibrinogen A gives the amount of lysed fibrinogen in 2 hours at 37° C. Fibrinogen B gives the fibrinogen concentration at the moment of sampling.The method is recommended to be used for evaluation of the true plasma fibrinogen level and the degree of fibrinogenolytic activity. This is particularly important during thrombolytic therapy.